Controlled synthesis of α-Fe2O3 nanostructures with the assistance of ionic liquid and their distinct photocatalytic performance under visible-light irradiation. Issue 5 (23rd December 2014) - Xie, Shuting; Jia, Han; Lu, Fei; Sun, Nan; Yu, Jierui; Liu, Shaojie; Zheng, Liqiang
Abstract : Different shaped α-Fe2 O3 nanostructures are controllably synthesized with the assistance of an ionic liquid, and their photocatalytic performance has also been investigated. Abstract : Well-dispersed α-Fe2 O3 nanostructures with controlled dimensionality and shape have been successfully prepared via a facile and environmentally friendly solvothermal route with the assistance of 1- N -butyl-3-methylimidazolium benzoate ([Bmim][PhCOO]). A significant advancement has been made in tailoring dendritic α-Fe2 O3 nanostructures along 10̄10 directions. The dendrites can be tailored to hexagonal plates and rods only by changing the molar ratio of [Bmim][PhCOO] to K3 [Fe(CN)6 ] from 0 : 1 to 2 : 1, and 5 : 1. [Bmim][PhCOO] is found to play a key role in the evolution of α-Fe2 O3 with different shapes: the nucleation rate is influenced by the hydrolysis of [PhCOO] − anions, and the [Bmim] + cations can favorably stabilize the 10̄10 facets due to the hydrogen bond- co -π–π stacking interaction. A possible mechanism was proposed. Furthermore, the visible light induced photodegradation of RhB reveals that α-Fe2 O3 rods exhibit higher photocatalytic activity compared to dendrites and plates. Interestingly, with the process proceeding, the photoactivity of these samples increases successively. The enhancement of photocatalytic performance may be due to the different exposed crystal facets of α-Fe2 O3 nanostructures and the degree of crystallinity. The tailoring process gives us an in-depth understanding of the formation mechanism of dendritic α-Fe2 O3 structures, which is not possibly achieved by the traditional time-dependent method, and it is highly expected that this study will suggest a promising new strategy for engineering practical photocatalysts for wastewater treatment.